2011
DOI: 10.1111/j.1532-950x.2011.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Fracture in Dogs with Suspected or Confirmed Osteosarcoma

Abstract: Treatment of pathologic fracture associated with presumptive osteosarcoma should be considered as an option to amputation or euthanasia if owners desire other options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
16
0
1
Order By: Relevance
“…All neoplastic antebrachia, with one exception, failed by crushing and/or bending at the OSA site, in the distal metaphysis of the radius. This failure pattern indicates that the OSA lesion forms the weakest part of the antebrachium, matching clinical observations described by others . By contrast, normal antebrachia failed by mid‐diaphyseal fractures, consistent with bending during axial compression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All neoplastic antebrachia, with one exception, failed by crushing and/or bending at the OSA site, in the distal metaphysis of the radius. This failure pattern indicates that the OSA lesion forms the weakest part of the antebrachium, matching clinical observations described by others . By contrast, normal antebrachia failed by mid‐diaphyseal fractures, consistent with bending during axial compression.…”
Section: Discussionsupporting
confidence: 87%
“…In situ therapies for OSA, if confirmed to induce an anti‐tumor immune response reducing distant tumor growth, may improve long‐term outcomes compared to other limb salvage options, in the subset of canine OSA patients at low risk for pathologic fracture. Early reports have described the successful treatment of pathologic fractures associated with appendicular neoplasia in dogs, as well as pre‐emptive support of tumor‐bearing bone with internal fixation . At this time, biomechanical loads leading to pathologic fracture in tumor‐bearing bone are unknown in the dog, and no criteria has been established to assess the risk of pathologic fractures in veterinary patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6,7,[9][10][11] We did not identify any significant difference in the fracture rate for the other tumor types found, but this may be secondary to the very low number of cases for the other types of neoplasms in this series. This is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…In veterinary medicine, there is little in the reported literature on the incidence of pathological fractures associated with primary bone tumors, [9][10][11] and reports are limited to small case series. A single study 9 evaluating pathological fractures in long bones reported that they accounted for < 3% of all fractures, but that > 90% of these were secondary to neoplasia in a series of 568 dogs in 1987.…”
mentioning
confidence: 99%
“…These include heart disease, osteosarcoma, bronchopneumonia, and gastric dilation-volvulus [1, 12–14]. Canine osteosarcoma often results in euthanasia due to poor quality of life in affected dogs and survival following diagnosis is typically less than one year [12, 15, 16]. In contrast, the prognosis of dogs with heart disease such as atrial fibrillation or DCM is better when diagnosed and treated early with median time to death reported to be up to 4 years following early heart disease diagnosis [17].…”
Section: Introductionmentioning
confidence: 99%